PERAN KEPEMIMPINAN CAMAT DALAM MENINGKATKAN EFEKTIVITAS PELAYANAN PERIZINAN KECAMATAN CUGENANG KABUPATEN CIANJUR - Rachmat Rachmat; Tantan Nurhasan; Mylda Noor Kamalia (PT. ABIG RIZKY PUBLISHER, 2025)
This study aims to analyze the influence of sub-district head (Camat) leadership and the quality of civil servant services on the effectiveness of licensing services in Cugenang Sub-district, Cianjur Regency. The research employs a quantitative approach with explanatory research design, using the community as the unit of analysis. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS). The results indicate that the leadership of the Camat plays an important role in improving service effectiveness through the ability to direct, coordinate, and supervise administrative staff. Meanwhile, the quality of public service delivered by civil servants is a more dominant factor in determining the success of licensing services, particularly in terms of responsiveness, professionalism, transparency, and community satisfaction. The synergy between effective leadership and high-quality service delivery contributes to more optimal, efficient, and community-oriented public services. This study provides theoretical contributions to the development of public service models based on local leadership and practical implications for local governments in improving licensing service quality.